Phosphonopeptides as substrates for peptide transport systems and peptidases of Escherichia coli. - Atherton, F R (1983)
Peptide transport and peptidase susceptibility of the antibacterial agent alafosfalin and other phosphonopeptides have been characterized in Escherichia coli. Phosphonodipeptides were accumulated by a process which appeared to involve multiple permeases; saturation was not achieved even at concentrations of 128 microM. Competition studies showed that these compounds had only a low affinity for the system transporting phosphonooligopeptides and were rapidly taken up by and were inhibitory to E. coli mutants unable to transport the toxic peptide triornithine. Phosphonodipeptides containing D-residues were not appreciably transported. By contrast, phosphonooligopeptides were generally transported by a distinct saturable permease system for which they had a high affinity. This system was identical to that utilized by triornithine. Phosphonooligopeptides with simple monoalkyl substituents at the amino terminus were also transported except in the case of a t-butyl substituent. The oligopeptide permease was also able to transport certain derivatives which contained some residues having D rather than L stereochemistry. Intracellular metabolism of phosphonooligopeptides was initiated almost exclusively by hydrolysis from the N terminus by an L-specific peptidase. This initial hydrolytic activity was unaffected by the aminopeptidase inhibitor bestatin, unlike the final hydrolysis step which yields L-1-aminoethylphosphonic acid from the phosphonodipeptide intermediate.